Urban Land Management and Housing Informality in Kenya: A Case of Eldoret Urban Area - Ong’anya, D. O.; Wakhungu, J. W.; China, S. S. (Africa Environmental Review Journal, 2021)
The informality in housing generally tends to complicate the urban land management in many cities of the world. Urban land management aims at the provision of affordable urban land in sufficient quantities and also aims at guiding the growth of cities and ensuring their efficient functioning. Eldoret Urban Area, is the previous Eldoret Municipality, established by the colonial government as an urban center in 1908 and as per the population census of 2009, has a population of 497,446. It has been growing at 6% and is one of the significant urban centers in the North-Rift in terms of industrial, academic, administration and business development. This study used The Becker and Selod (2009), dual- market framework model of urban economic theory to informality. This model emphasis that different levels of risk aversion or other differences among households would be a sufficient but not necessary condition for the two markets (i.e. formal and informal) to co-exist. The urban economic models- The Brueckner and Selod (2009), make assumptions that are at odds with the reality in most developing world cities. The model also assumed all land is fully serviced and that the rental market is complete. However, the housing strategies of significant segment of the urban population in developing countries violate many of these conditions. Economics models of the informal housing markets assume implicitly or explicitly; the residents can afford to live in the formal market but stay in informal settlements for institutional reasons (such as community ties, inertia and lower risk aversion) or for purely opportunistic reasons. Urban Residents that are unable to bid competitively in formal markets use variety of strategies to gain housing occupying areas not open to formal markets for instant, environmentally protected zone occupying areas not yet urbanized, thereby saving on the serving costs transferred by developers; crowding into existing buildings and building progressively overlong period. To overcome the negative consequences of housing informality and to ensure appropriate management of urban land management, this paper tends to explores the applications of traditional policy approaches to informality, which aims at increasing the capacity of low income families to pay for housing, while also holding down the prices of housing and serviced land. The key policy alternatives considered under this discussion are; transportation costs as a substitute credit system; the property tax as a planning tool and using value capture to fund urban services. In conclusion, it is true that informality is a problem of land market management that urban economic theory has yet to explain, if the urban households both poor and rich to be provided with affordable and quality housing in our cities.